The role of varus and valgus alignment in the initial development of knee cartilage damage by MRI: the MOST study. Issue 2 (1st May 2012) - Sharma, Leena; Chmiel, Joan S; Almagor, Orit; Felson, David; Guermazi, Ali; Roemer, Frank; Lewis, Cora E; Segal, Neil; Torner, James; Cooke, T Derek V; Hietpas, Jean; Lynch, John; et al.
Abstract : Objective: Varus and valgus alignment are associated with progression of knee osteoarthritis, but their role in incident disease is less certain. Radiographic measures of incident knee osteoarthritis may be capturing early progression rather than disease development. The authors tested the hypothesis: in knees with normal cartilage morphology by MRI, varus is associated with incident medial cartilage damage and valgus with incident lateral damage. Methods: In MOST, a prospective study of persons at risk of or with knee osteoarthritis, baseline full-limb x-rays and baseline and 30-month MRI were acquired. In knees with normal baseline cartilage morphology in all tibiofemoral subregions, logistic regression was used with generalised estimating equations to examine the association between alignment and incident cartilage damage adjusting for age, gender, body mass index, laxity, meniscal tear and extrusion. Results: Of 1881 knees, 293 from 256 persons met the criteria. Varus versus non-varus was associated with incident medial damage (adjusted OR 3.59, 95% CI 1.59 to 8.10), as was varus versus neutral, with evidence of a dose effect (adjusted OR 1.38/1° varus, 95% CI 1.19 to 1.59). The findings held even excluding knees with medial meniscal damage. Valgus was not associated with incident lateral damage. Varus and valgus were associated with a reduced risk of incident lateral and medial damage, respectively. Conclusion: In knees with normal cartilage morphology, varus was associated with incident cartilage damage in the medial compartment, and varus and valgus with a reduced risk of incident damage in the less loaded compartment. These results support that varus increases the risk of the initial development of knee osteoarthritis.